Studies on the supramolecular complex of a guanosine with beta-cyclodextrin and evaluation of its anti-proliferative activity - Prabu, S. (Elsevier Ltd, 2020)
The behavior of the inclusion behavior of guanosine (GU) with beta-cyclodextrin (Î²-CD) in the liquid, solid and virtual state were investigated. The absorption and fluorescence spectral were used to determine the inclusion behavior in liquid state. FT-IR, NMR, TGA, DSC, PXRD and FESEM techniques were used to investigate the inclusion behavior in solid-state, meanwhile the virtual state studies are done by molecular docking. The solid inclusion complex (GU: Î²-CD) was prepared by using the co-precipitation method. The binding constant (K) of (GU: Î²-CD) was calculated by using Benesi-Hildebrand. Besides that, the 1:1 stoichiometric ratio of inclusion complex was confirmed by using the Benesi-Hildebrand plot and Job's plot of continuous variation method. The most preferable model of GU: Î²-CD that suggested via molecular docking studies was in good agreement with experimental results. The inclusion complex of GU: Î²-CD exerted its toxicity effects towards HepG2 cell lines based on the reduced number of cell viability and lowest IC50 value compared to the GU and Î²-CD viability. Â© 2020 Elsevier Ltd